Quadrigeminal plate arachnoid cyst presenting with eye movement related migraine: a rare case report (Medical Journal of Indonesia, 2023)
Type II arachnoid cyst of the quadrigeminal cistern is the rarest type of arachnoid cyst (10% prevalence) in adults and is generally asymptomatic. We reported an unusual case of chronic right-sided migraine provoked by right eye adduction, right eye adduction soreness, and dry eye symptoms in a 47-year-old woman with quadrigeminal arachnoid cyst confirmed by radiological findings with the compression of the tectal plate, vermis, and superomedial cerebellum’s part. She was treated conservatively without improvement for 1 year before surgical intervention was conducted. Microsurgery for cyst excision and fenestration was done, followed by immediate relief from all her complaints after 3 months of follow-up. These findings should help clinicians consider surgical intervention for patients with chronic symptoms related to nerve function that have no improvement with the initial treatment.